The epidemiology of MRI-detected pelvic injuries in athletes in the Rio de Janeiro 2016 Summer Olympics. Issue 105 (August 2018) - Heiss, Rafael; Guermazi, Ali; Jarraya, Mohamed; Engebretsen, Lars; Roemer, Frank W.
Abstract: Objective: To describe the prevalence, severity and location of pelvic injuries, including hip, muscle and tendon pathologies, as assessed on MRI in athletes participating in the Rio de Janeiro 2016 Summer Olympic Games. Methods: We analyzed all pelvic MRIs that were acquired for suspected injury as reported by the National Olympic Committee (NOC) medical teams and the Organizing Committee medical staff during the Rio 2016 Summer Olympics. Diagnostic imaging was performed through the Olympic Village Polyclinic, using 3 T and 1.5 T MR scanners. Images were interpreted retrospectively according to standardized criteria. Results: A total of 11, 274 athletes participated in the Games, of which 40 (0, 4%) were referred for a pelvic MRI. Thirty-seven of the 40 (92%) had at least one abnormal finding, and some had as many as 17, for an average of 4.1 pathologies per examination. Almost half of all abnormal findings were assessed as pre-existing (46%). The majority of acute/subacute injuries were observed in track and field athletes (44%), whereas the highest number of pre-existing findings was seen in ball-sports athletes (39%). Forty-seven per cent of all acute/subacute injuries were muscle injuries with the gluteus maximus muscle the most commonly affected. In contrast, most pre-existing findings were detected at the symphysis (59%). Conclusion: Our study demonstrated a high prevalence of both acute/subacute injuries and chronic changes in Olympic athletes undergoing pelvic MRI. Muscle injuries were the most common acute injuries, found mainly in track and field athletes. Most chronic changes were identified at the symphysis region in ball-sports athletes.